The design of a monostatic, ultra wide band,VHF, pulse radar for detection of close-in targets - Van der Merwe, P. J. (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2003.